Backstepping multiphase induction machine control impact in presence of open phases fault - Berrahal, Chaker; El Fadili, Abderrahim (Institute of Advanced Engineering and Science, 2025)
As power requirements increase, multiphase induction machines (MPIMs) present a promising alternative to conventional three-phase induction machines. These machines help reduce the current switched by the inverter and circulating through the windings, which in turn mitigates torque ripple. Moreover, incorporating more than three phases enhances system reliability, allowing the machine to maintain operation even in the event of one or more phase failures. This makes MPIMs particularly suitable for high-reliability applications, such as electric vehicles. While most previous studies have concentrated on speed and flux control of MPIMs, less attention has been given to handling open-phase faults. This paper explores the robustness of the backstepping control method applied to MPIMs, particularly in scenarios involving open-phase faults. The proposed multi-loop nonlinear controller is developed to achieve two main objectives: precise speed regulation across a wide range of speed references, and effective rotor flux control. The convergence of the feedback control system is rigorously analyzed using Lyapunov’s stability theory. Simulation results show that, although the control objectives are met, stator current demands increase as more phases experience faults. This observation highlights the need for further development of MPIM models that take phase faults into consideration.